The three types of interference errors in numerical expression by Vietnamese EFL speakers - DANG, NHON (Advances in Social Sciences Research Journal, 2021)
This paper aims to investigate numerical expression by Vietnamese speakers of English as a foreign language (EFL). The study identifies and explains the causes of interference errors in expressing number of nouns. A descriptive-cognitive research design was conducted error-oriented investigation of 62 high-school students and 30 employees working in English-speaking companies participating in writing a 45-minute essay for numerical errors from the essays collected. The findings revealed that Vietnamese EFL speakers had difficulty in expressing the number of the entities represented by the nouns due to differences in means and manner of numerical expression in English whose sentences are numerically compulsory and grammatically relevant as opposed to those in Vietnamese whose numerical category is grammatically unimportant, but lexically relevant, and seen with number-neutral nouns or general numbers. Errors also occurred as Vietnamese EFL speakers failed to acquire the count-uncount distinction due in part to differences in perceptualizing the numerical meaning of the entities represented by nouns, ascribing the countability wrong and keeping the same property of countable/uncountable nouns despite having referred to different referents. The paper ended with some pedagogical implications to help Vietnamese EFL speakers improve numerical errors when using English.